Out-of-Register Parallel β-Sheets and Antiparallel β-Sheets Coexist in 150-kDa Oligomers Formed by Amyloid-β(1–42). Issue 16 (24th July 2020) - Gao, Yuan; Guo, Cong; Watzlawik, Jens O.; Randolph, Peter S.; Lee, Elizabeth J.; Huang, Danting; Stagg, Scott M.; Zhou, Huan-Xiang; Rosenberry, Terrone L.; Paravastu, Anant K.
Abstract: We present solid-state NMR measurements of β-strand secondary structure and inter-strand organization within a 150-kDa oligomeric aggregate of the 42-residue variant of the Alzheimer's amyloid-β peptide (Aβ(1–42)). We build upon our previous report of a β-strand spanned by residues 30–42, which arranges into an antiparallel β-sheet. New results presented here indicate that there is a second β-strand formed by residues 11–24. Contrary to expectations, NMR data indicate that this second β-strand is organized into a parallel β-sheet despite the co-existence of an antiparallel β-sheet in the same structure. In addition, the in-register parallel β-sheet commonly observed for amyloid fibril structure does not apply to residues 11–24 in the 150-kDa oligomer. Rather, we present evidence for an inter-strand registry shift of three residues that likely alternate in direction between adjacent molecules along the β-sheet. We corroborated this unexpected scheme for β-strand organization using multiple two-dimensional NMR and 13 C– 13 C dipolar recoupling experiments. Our findings indicate a previously unknown assembly pathway and inspire a suggestion as to why this aggregate does not grow to larger sizes. Graphical abstract: Unlabelled Image Highlights: The assembly pathways and structural details of Aβ oligomers are not understood. Two β-strand regions were located on the Aβ(1–42) sequence in 150-kDa oligomers. The N-strand (E11–V24) was characterized to arrange into out-of-register parallel β-sheets. The out-of-register parallel β-sheets and the antiparallel β-sheets coexist in the oligomer structure. The co-existence of β-sheets with distinct organizations may differentiate oligomer and fibril assembly pathways.